Assessment of Inflammatory Markers IL- 6 and TNF- Alpha in Newly Diagnosed Type II Diabetics without Hypertension in Comparison with Non-Diabetic Normotensive Subjects (Academia Journal of Medicine, 2020)
Background: The present study was conducted to assess inflammatory markers IL- 6 and TNF- alpha in newly diagnosed type II diabetics without hypertension. Subjects and Methods: 68 types of II diabetes mellitus patients and equal numbers of normotensive non-diabetic subjects were also recruited. Glycated hemoglobin (HbA1c) levels, TNF- alpha and IL- 6 were determined. Results: The mean IL- 6 level in group I was 17.4 pg/ml and in group II was 4.2 pg/ml. TNF- alpha level in group I was 35.8 pg/ml and in group II was 12.5 pg/ml. The difference was significant (P< 0.05). Conclusion: TNF- alpha and IL- 6 level was higher among diabetic patients as compared to healthy normotensive non-diabetic subjects.
Keywords: Diabetic; Normotensive; TNF- alpha